E-Health Readiness Scale of Health Institutions: Development, Validity and Reliability - Gündoğdu, Gülşen; Ayden, Cem (My University, 2025)
The use of information and communication technologies, known as e-health, in healthcare services is increasing rapidly every day. The aim of this study is to develop a measurement tool that can evaluate the readiness of health institutions for e-health applications and to test its validity and reliability. Exploratory sequential mixed method research was preferred as the research method. Within the scope of the research, primarily the qualitative research phase was conducted. At this stage, semi-structured interviews were held with eight experts in the relevant field. The data obtained from the expert interviews were transferred to the MAXQDA 2020 program and analyzed. At this stage, an item pool consisting of six sub-dimensions and 40 items regarding the e-health readiness scale of health institutions was created. As a result, the draft scale consisting of 40 items; After expert opinion and content validity stages, it was reduced to 33 items. The draft scale of e-health readiness of the discovered health institutions was applied on a suitable sample at the quantitative research stage and the reliability and construct validity of the scale was examined. Statistical analyzes were carried out using the R-Project 2021 program and lavaan 2012 package. The confidence level in the study was evaluated as 95%. As a result of these analyses, the e-health readiness scale of health institutions consists of four sub-dimensions and 25 items: acceptance and readiness for use, self-sufficiency, technology and infrastructure readiness and structural readiness.
Keywords: Mixed methods; information and communication technologies; e-health; health institutions.